ducational Challenges of the Minority Educational Institutions at Odisha - Gangmei, Elizabeth (JOURNAL OF INDIAN EDUCATION, 2018)
Education for all is an aspiration and commitment of India since the inception of the constitution. The journey of making education a fundamental right at the elementary level is a proof which indicates the seriousness and commitment of the nation. In spite of the efforts taken, accessibility to quality education for all continues to remain a vision. To begin with, it is necessary to identify where the standard of education of the minorities lie. At the same time, it is pertinent to understand that India is constituted of a diverse community wherein the challenges in each community are unique. The minority communities having a distinct religious, linguistic and cultural background are a persistent source of concern as they continue to lag behind in educational progress. Many a time, these challenges are attributed to isolation and disadvantaged situation as seen in the government documents, reports and literacy census. These necessitate for exploration and critical analysis of the actual position that exist particularly in the educational sector. On the background of the issues raised, the study was confined to Muslim and Christian minority schools of Odisha at the elementary level, selected by purposive sampling and analysed, both quantitatively and qualitatively. The findings indicate that there is a challenge in the areas of infrastructure, teacher appointment and lack of in-service professional development opportunities. Isolation from the mainstream society in the larger context is yet another challenge. Findings are discussed for the overall educational development that has an implication for various other minorities also.